Rural radio outreach - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In November 1994 a workshop was held in Port of Spain, Trinidad for 14 rural broadcasters from 10 countries in the English speaking Caribbean